The Effectiveness of Applying the Iqra’ Method in Accelerating the Ability to Read the Qur’an in the “Al-Hanif” Middle School for Girls in Cilegon for the Year 2023/2024: فعالية تطبيق طريقة اقراء في إسراع القدرة على قراءة القرآن في المدرسة المتوسطة "الحنيف" للبنات في تشيليغون للعام 2023/2024 - Siti Mufarokah; Isfaizah Isfaizah; Bakri Mohammed Bakheet Ahmed (ZAD Al-Mufassirin, 2025)
Every Muslim is supposed to be able to read the Holy Qur’an according to the rules of Tajweed. This study examined the effectiveness of applying the Iqra method in accelerating the ability to read the Qur’an in Tahseen at the “Al-Hanif” School for Girls in Cilegon for the year 2023/2024. The study focused on female students who suffer from difficulties in reading correctly. The study used a qualitative and quantitative methodology, and research data was collected through observation, interviews, or reviewing documents from various elements present on the research site. The result showed that the method used in applying the book “Iqraa” is the method using simulation, oral speech, explicit speech, and questioning for educational purposes, as well as the presence of a statistically significant difference between the results of the pre- and post-test. The study concluded that the Iqraa method represents an effective tool in accelerating the improvement of reading ability.